EVALUATION OF ALTERNATIVE CONFIGURATIONS OF A WATER-OIL HEAT EXCHANGER SYSTEM - Gonçalves A. L. V.; Francisco, A. S. (Revista de Engenharia Térmica, 2016)
The success in performance of equipment at industrial facilities is associated with its capacity of normal operation. When some equipment is subject to maintenance at large cost, the operation is uninteresting or even impracticable. The heat exchanger is an equipment widely employed, which performs transfer of heat between two fluids at different temperatures, separated by a solid wall. In this work, we evaluate alternative configurations of a system of shell-and-tube heat exchangers, aiming to improve the performance of this system in economical point of view, and to mitigate the maintenance cost. We use the effectiveness method to obtain outlet temperature values, and compare such results with values measured in situ. We conclude that alternative configurations are feasible in order to improve the thermal performance of the system of heat exchangers, reducing installation cost.